Effects of CO2 Changes on Hyperspectral Infrared Radiances and Its Implications on Atmospheric Temperature Profile Retrieval and Data Assimilation in NWP - Di Di; Yunheng Xue; Jun Li; Wenguang Bai; Peng Zhang (Remote Sensing, 2020)
Although atmospheric CO2 is a trace gas, it has seasonal variations and has increased over the last decade. Its seasonal variation and increase have substantial radiative effects on hyperspectral infrared (IR) radiance calculations in both longwave (LW) and shortwave (SW) CO2 absorption spectral regions that are widely used for weather and climate applications. The effects depend on the spectral coverage and spectral resolution. The radiative effect caused by the increase of CO2 has been calculated to be greater than 0.5 K within 5 years, whereas a radiative effect of 0.1–0.5 K is introduced by the seasonal variation in some CO2 absorption spectral regions. It is important to take into account the increasing trend and seasonal variation of CO2 in retrieving the atmospheric temperature profile from hyperspectral IR radiances and in the radiance assimilation in numerical weather prediction (NWP) models. The simulation further indicates that it is very difficult to separate atmospheric temperature and CO2 information from hyperspectral IR sounder radiances because the atmospheric temperature signal is much stronger than that of CO2 in the CO2 absorption IR spectral regions.